2005
DOI: 10.1177/0363546504273487
|View full text |Cite
|
Sign up to set email alerts
|

Medial Collateral Ligament Reconstruction Using Autogenous Hamstring Tendons

Abstract: Although this is a short-term follow-up study involving a small number of cases, we considered our procedure to be an effective method of surgically restoring the function of the medial collateral ligament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
119
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 28 publications
3
119
2
4
Order By: Relevance
“…However, MCL repair is not a good choice in a subacute time frame because the MCL would have incomplete healing and scarring and would be very difficult to identify in a subacute time frame; revision of those structures could hardly yield a satisfactory clinical result. [11][12][13] More importantly, from a functional perspective, the MCL and ACL both contribute to maintaining rotational stability, 1,2,14,15 and the rotatory instability would be aggravated if these 2 structures were simultaneously injured. However, Grant et al did not address how to solve the problem of rotatory instability when it is present on physical examination.…”
mentioning
confidence: 99%
“…However, MCL repair is not a good choice in a subacute time frame because the MCL would have incomplete healing and scarring and would be very difficult to identify in a subacute time frame; revision of those structures could hardly yield a satisfactory clinical result. [11][12][13] More importantly, from a functional perspective, the MCL and ACL both contribute to maintaining rotational stability, 1,2,14,15 and the rotatory instability would be aggravated if these 2 structures were simultaneously injured. However, Grant et al did not address how to solve the problem of rotatory instability when it is present on physical examination.…”
mentioning
confidence: 99%
“…La reconstrucción del LCM utilizando injerto autólogo de isquiotibiales ha sido reportada con buenos resultados funcionales en pacientes con lesiones crónicas del LCM. Yoshiva et al (20) analizaron 12 pacientes a los que se les realizó una reconstrucción simultánea de ambas lesiones ligamentosas, utilizando injerto de semitendinoso autólogo para el LCM y tendón rotuliano para el LCA. Con un seguimiento mínimo de 2 años, los autores reportaron una movilidad normal/casi normal en todos sus pacientes, con una función normal/casi normal en el 92% mediante la escala de IKDC.…”
Section: Discussionunclassified
“…Sin embargo, existe evidencia de que en lesiones asociadas de LCA y LCM de grado III, la reparación aislada del LCA se relaciona con mayor carga mecánica sobre el LCA reconstruido, aumentando el riesgo de falla y de inestabilidad crónica sintomática en valgo de la rodilla (16)(17)(18) . La reconstrucción simultánea de LCA y LCM en lesiones asociadas ha sido descrita con buenos resultados funcionales (8,19,20) . Resultados: todos los pacientes mejoraron significativamente en los scores funcionales y las maniobras de estabilidad.…”
Section: Introductionunclassified
“…[38,2,8] Few biomechanically validated anatomic reconstruction techniques using quantitatively described anatomic data [22,37] to design reconstruction techniques of the sMCL and POL injuries have been reported. An anatomic reconstruction technique is preferable because it has been demonstrated that anatomic ligament reconstructions better approximate normal knee biomechanics [6,3] The purpose of this review is to present anatomical and biomechanical background for anteromedial rotatory instability including surgical management strategies and clinical outcomes of different surgical techniques.…”
Section: Introductionmentioning
confidence: 99%